2013
DOI: 10.1002/ijc.28445
|View full text |Cite
|
Sign up to set email alerts
|

A model of liver carcinogenesis originating from hepatic progenitor cells with accumulation of genetic alterations

Abstract: Activation-induced cytidine deaminase (AID) contributes to inflammation-associated carcinogenesis through its mutagenic activity. In our study, by taking advantage of the ability of AID to induce genetic aberrations, we investigated whether liver cancer originates from hepatic stem/progenitor cells that accumulate stepwise genetic alterations. For this purpose, hepatic progenitor cells enriched from the fetal liver of AID transgenic (Tg) mice were transplanted into recipient "toxin-receptor mediated conditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Consistently, AID expression is observed in hepatocytes of chronically inflamed HCV-infected liver, while AID expression is not observed in normal liver tissues [126,127]. In vivo studies revealed that constitutive AID expression promotes tumorigenesis by enhancing the susceptibility to mutagenesis in a variety of epithelial organs, including the liver [125,128,129]. These findings suggest that chronic inflammation caused by HCV infection triggers the aberrant upregulation of AID in hepatocytes, leading to the genomic instability required for tumorigenesis.…”
Section: Genetic Alterations Accumulated In Hepatitis Virusinfected Lmentioning
confidence: 75%
“…Consistently, AID expression is observed in hepatocytes of chronically inflamed HCV-infected liver, while AID expression is not observed in normal liver tissues [126,127]. In vivo studies revealed that constitutive AID expression promotes tumorigenesis by enhancing the susceptibility to mutagenesis in a variety of epithelial organs, including the liver [125,128,129]. These findings suggest that chronic inflammation caused by HCV infection triggers the aberrant upregulation of AID in hepatocytes, leading to the genomic instability required for tumorigenesis.…”
Section: Genetic Alterations Accumulated In Hepatitis Virusinfected Lmentioning
confidence: 75%
“…This phenomenon was originally observed in bacteria , where genes transcribed during the stress response were more likely mutated than untranscribed genes. Transcription‐associated mutations have also been observed in yeast and mammalian cells . In this mechanism, mutations are targeted to expressed genes, the products of which are needed as part of adaptive programs.…”
Section: Programmed Stress Responsesmentioning
confidence: 99%
“…Insights & Perspectives ..... genes. Transcription-associated mutations have also been observed in yeast [64] and mammalian cells [65]. In this mechanism, mutations are targeted to expressed genes, the products of which are needed as part of adaptive programs.…”
Section: A Cipponi and D M Thomasmentioning
confidence: 99%
“…Furthermore, whole exome sequencing of tumor cells allowed us to determine the landscape of the accumulated genetic alterations during tumorigenesis and clarified that several dozen genes acquired single nucleotide variants in tumor tissues originating from the transplanted hepatic progenitor cells of AID Tg mice. Pathway analysis using a KEGG database revealed that the acquired genetic aberrations affected several important signaling pathways, thereby disturbing normal homeostasis [31]. These results indicate that accumulation of genetic alterations in fetal hepatic progenitor cells could lead to HCC development.…”
Section: Novel Mouse Models With Stepwise Accumulation Of Genetic Altmentioning
confidence: 99%
“…We enriched hepatic progenitor cells from the E13.5 fetal liver of AID Tg mice and transplanted those cells, which have enhanced liver regeneration activity, into recipient mice. HCC developed in 7 out of 11 (63.6%) recipient mice receiving enriched hepatic progenitor cells from AID Tg mice, whereas no tumorigenesis was observed in recipient mice transplanted with hepatic progenitor cells from wild-type mice (control) [31]. Furthermore, whole exome sequencing of tumor cells allowed us to determine the landscape of the accumulated genetic alterations during tumorigenesis and clarified that several dozen genes acquired single nucleotide variants in tumor tissues originating from the transplanted hepatic progenitor cells of AID Tg mice.…”
Section: Novel Mouse Models With Stepwise Accumulation Of Genetic Altmentioning
confidence: 99%